Rendements d’utilisation et consommation d’énergie au Québec - Truong, Thuan-Van; Nguyen, The-Hiep (L'Actualité économique)

(untitled) (HEC Montréal, 1980)
AbstractThe concept of useful energy consumption has been used by some authors by weighting observed energy consumptions. It is argued in this paper that the weights should not be the regression parameter estimates of the GNP on various forms of energy consumptions as they are now, but they should be the mechanical use efficiency of each energy form. A number of functional forms of the GNP are then obtained, all very good from the econometric viewpoint. Finally, it is pointed out that the rate of substitution between different forms of energy does depend on the functional form of the GNP